Unraveling Indonesia's Diplomacy in the Pacific Region - Pugu, Melyana Ratana (International Journal of Social Service and Research, 2024)
This research aims to examine Indonesia's diplomacy in the Pacific Region, specifically during the Joko Widodo administration, focusing on the period spanning the last two decades. Emphasizing the significance of the Pacific Region in Indonesia's current foreign policy, the study employs qualitative research methods, utilizing international relations analysis, to explore diplomatic and cooperative efforts. Data for this study are derived from extensive literature reviews, including journals, books, regulations, and internet sources. The findings indicate that Indonesia, through its "look east" policy, has increasingly considered the Pacific Region pivotal for economic development, connectivity, and security. Notably, Indonesian diplomacy in the Pacific has evolved, with recent efforts showcased during Indonesia's chairmanship in Asean and the Asean-43 Summit. The latter has positioned the Pacific/Indo-Pacific Region as the Epicentrum of Growth, emphasizing its centrality for development and connectivity with ASEAN member countries and dialogue partner nations, such as China, Japan, and South Korea. In conclusion, this research sheds light on the evolving nature of Indonesia's diplomacy in the Pacific Region, offering insights into the country's strategic approach to fostering relations, economic development, and regional cooperation.